'Raising the Pulse': The environmental, nutritional and health benefits of pulse‐enhanced foods. Issue 1 (17th January 2023) - Lovegrove, Julie A.; O'Sullivan, Donal M.; Tosi, Paola; Millan, Elena; Todman, Lindsay C.; Bishop, Jacob; Chatzifragkou, Afroditi; Clegg, Miriam E; Hammond, John; Jackson, Kim G.; Jones, Philip J.; Lignou, Stella; et al.
Abstract: Diet is a key modulator of non‐communicable diseases, and food production represents a major cause of environmental degradation and greenhouse gas emissions. Yet, 'nudging' people to make better food choices is challenging, as factors including affordability, convenience and taste often take priority over the achievement of health and environmental benefits. The overall 'Raising the Pulse' project aim is to bring about a step change in the nutritional value of the UK consumers' diet, and to do so in a way that leads to improved health and greater sustainability within the UK food system. To achieve our objectives, UK‐specific faba bean production systems that optimise both end users' diets and environmental and economic sustainability of production will be implemented in collaboration with key stakeholders (including industry, the retail sector and government). Palatable faba bean flours will be produced and used to develop 'Raising the Pulse' food products with improved nutritional profile and environmental value. Consumer focus groups and workshops will establish attitudes, preferences, drivers of and barriers to increased consumption of such products. They will inform the co‐creation of sensory testing and University‐wide intervention studies to evaluate the effects of pulses and 'Raising the Pulse' foods on diet quality, self‐reported satiety, nutritional knowledge, consumer acceptance and market potential. Nutrient bioavailability and satiety will be evaluated in a randomised‐controlled postprandial human study. Finally, a system model will be developed that predicts changes to land use, environment, business viability, nutrition and human health after substitution of existing less nutritionally beneficial and environmentally sustainable ingredients with pulses. Government health and sustainability priorities will be addressed, helping to define policy‐relevant solutions with significant beneficial supply chain economic impacts and transformed sustainable food systems to improve consumer diet quality, health and the environment.